THE INFLUENCE OF ORGANIZATIONAL CULTURE, LEADERSHIP STYLE AND EMPLOYEE ENGAGEMENT ON THE PERFORMANCE OF MILLENIAL EMPLOYEE (CASE STUDY AT PT. RITEL GLOBAL SOLUSI EMPLOYEES) - Yudi Nugroho; Farida Elmi (Dinasti Publisher, 2022)
The failure to achieve the work performance target causing by the decline in employee performance, which is dominated by the millennial generation, is the background of this phenomenon in a company. This research aims to measure how the influence of organizational culture, leadership style and employee engagement affecting the performance of millennial generation employees at PT Ritel Global Solusi. This research type was included in quantitative research and the data analysis through multiple linear regression with the research sample was 93 employees as the millennial generation category. The results of multiple linear regression analysis shows that organizational culture and employee engagement have a significant impact on employee performance, while leadership style has in significant impact on employee performance.